Urban Chinese Daughters Navigating New Roles, Status and Filial Obligation in a Transitioning Culture - O'Neill, Patricia (St Antony's Series,, 2018)
The lives of urban Chinese daughters have changed. Education and employment have propelled them from dependency to self-sufficiency, resulting in new attitudes and lifestyles. However, traditional filial obligation has remained. This book asks why it continues and how it is currently discharged, focusing on the emotion work daughters do to sustain the parent relationship, deal with conflict and maintain their self-esteem. Based on interviews with women living in Hong Kong, Singapore and mainland China, the book further explores whether the structural or relational motivations underpinning support and care may be less important than the standards daughters impose on themselves; why care may be discontinued or not undertaken in the first place; why care provided to parents may be different from in-laws, and the importance of domestic helpers to the modern caregiving paradigm. To undertake this exploration, a typology of support and care was created, allowing for the first time to distinguish between what daughters do for healthy parents and in-laws versus parents who require temporary or full time care, specifically addressing how providing support and care affects the daughters' well-being.